New insights into the in vitro biological effects, in silico docking and chemical profile of clary sage – Salvia sclarea L. (August 2018) - Zengin, Gokhan; Senkardes, Ismail; Mollica, Adriano; Picot-Allain, Carene Marie Nancy; Bulut, Gizem; Dogan, Ahmet; Mahomoodally, M. Fawzi
Graphical abstract: Highlights: Biological, chemical and in silico fingerprints of Salvia sclerea were investigated. Methanol extract showed the highest phenolic and flavonoid contents. Water extract showed best activity against α-glucosidase and tyrosinase. Docking showed that quercetin binds to tyrosinase by two hydrogen and a pi-pi bonds. S. sclerea is a potent plant for possible biomedical applications Abstract: Salvia sclarea L. is traditionally used to manage common human ailments and is consumed as a food product. This study aimed to establish the phytochemical profile and antioxidant potential of ethyl acetate, methanol, and water extracts of Salvia sclarea . The inhibitory action of the extracts against α-amylase, α-glucosidase, acetylcholinesterase, butyrylcholinesterase, and tyrosinase was also investigated. Methanol extract showed the highest phenolic and flavonoid contents (81.78 mg GAE/g extract and 40.59 mg RE/g extract, respectively). Reversed phase high performance liquid chromatography with diode array detector analysis revealed that S. sclarea was rich in rosmarinic acid. The water extract exhibited the lowest inhibitory activity against α-amylase but the upmost activity against α-glucosidase (0.19 and 18.24 mmol ACAE/g extract, respectively). Experimental data showed that only the water extract (8.86 mg KAE/g extract) significantly inhibited tyrosinase. Docking studies showed that quercetin binds to tyrosinase by two hydrogen and a pi-pi bonds. Salvia sclarea showed interesting biological activity against key enzymes involved in the pathogenesis of common ailments.